On the Developmental and Environmental Regulation of Secondary Metabolism in Vaccinium spp. Berries - Karppinen, Katja (Front Plant Sci, 2016)
Secondary metabolites have important defense and signaling roles, and they contribute to the overall quality of developing and ripening fruits. Blueberries, bilberries, cranberries, and other Vaccinium berries are fleshy berry fruits recognized for the high levels of bioactive compounds, especially anthocyanin pigments. Besides anthocyanins and other products of the phenylpropanoid and flavonoid pathways, these berries also contain other metabolites of interest, such as carotenoid derivatives, vitamins and flavor compounds. Recently, new information has been achieved on the mechanisms related with developmental, environmental, and genetic factors involved in the regulation of secondary metabolism in Vaccinium fruits. Especially light conditions and temperature are demonstrated to have a prominent role on the composition of phenolic compounds. The present review focuses on the studies on mechanisms associated with the regulation of key secondary metabolites, mainly phenolic compounds, in Vaccinium berries. The advances in the research concerning biosynthesis of phenolic compounds in Vaccinium species, including specific studies with mutant genotypes in addition to controlled and field experiments on the genotype × environment (G×E) interaction, are discussed. The recently published Vaccinium transcriptome and genome databases provide new tools for the studies on the metabolic routes.